Eco-sustainable coatings based on chitosan, pectin, and lemon essential oil nanoemulsion and their effect on strawberry preservation - Abdalla, Gabriela [UNESP]; Mussagy, Cassamo Ussemane; Sant'Ana Pegorin Brasil, Giovana [UNESP]; Scontri, Mateus [UNESP]; da Silva Sasaki, Josana Carla [UNESP]; Su, Yanjin [UNESP]; Bebber, Camila [UNESP]; Rocha, Raildis Ribeiro [UNESP]; de Sousa Abreu, Ana Paula [UNESP]; Goncalves, Rogerio Penna [UNESP]; Burd, Betina Sayeg [UNESP]; Pacheco, Mariana Ferraz [UNESP]; et al. (Elsevier, 2023)
Films and coatings manufactured with bio-based renewable materials, such as biopolymers and essential oils, could be a sustainable and eco-friendly alternative for protecting and preserving agricultural products. In this work, we developed films and coatings from pectin and chitosan to protect strawberries (Fragaria x ananassa Duch.) from spoilage and microbial contamination. We developed three coatings containing equal amounts of glycerol and Sicilian lemon essential oil (LEO) nanoemulsion. We identified seventeen chemicals from LEO by GC–MS chromatogram, including D-limonene, α-Pinene, β-Pinene, and γ-Terpinene. The pectin and chitosan coatings were further characterized using different physicochemical, mechanical, and biological methods. The films demonstrated satisfactory results in strength and elongation at the perforation as fruit packaging. In addition, the coatings did not influence the weight and firmness of the strawberry pulps. We observed that 100 % essential oil was released in 1440 min resulting from the erosion process. Also, the oil preserved the chemical stability of the films. Antioxidant activity (AA), measured by Electron Paramagnetic Resonance (EPR), showed that the coatings loaded with 2 % LEO nanoemulsion (PC + oil) showed that almost 50 % of AA from LEO nanoemulsion was preserved. The chitosan and the pectin-chitosan coatings (PC + oil) inhibited filamentous fungi and yeast contaminations in strawberries for at least 14 days, showing a relationship between the AA and antimicrobial results.
Keywords: Edible coatings; Essential oil nanoemulsion; Fungi; Oil release; Postharvest preservation